Implantation of posterior chamber phakic intraocular lens for myopia and hyperopia - long-term clinical outcomes - Kocová, H; Vlková, Eva; Michalcová, L; Motyka, O (Journal français d'ophtalmologie, 2017)
PURPOSE: To evaluate long-term refractive outcomes of implantable collamer lens (ICL) implantation and late postoperative complications. METHODS: We assessed outcomes of patients who underwent ICL implantation (type ICM V4 for myopia, ICH V3 for hyperopia, TICM V4 for astigmatism) in our department between 1998 and 2013. It comprised 62 eyes (40 myopic and 22 hyperopic). The average follow-up period was 10.5 years. We evaluated: uncorrected and best-corrected visual acuity (UCVA and BCVA), spherical equivalent (SE), ICL vault, endothelial cell density and late postoperative complications. RESULTS: In myopes, the average UCVA was 1.0±0.37 and BCVA 1.18±0.38, in hyperopes 0.78±0.19 and 1.14±0.18, respectively. The average SE in myopes, whose target refraction was emmetropia, was -0.6±0.83 Dsf, in hyperopes +0.73±0.93. Central ICL vault was 206.16μm±105.94, (range 10-427) in myopes, 195.5μm±109.09, (range 20-404) in hyperopes. The most common late postoperative complication was cataract formation. Three myopic eyes (7.5%) developed symptomatic anterior subcapsular opacities with loss of at least two lines of BCVA. Cataract significantly affecting visual acuity occurred in 5 myopic eyes (12.5%) and 2 hyperopic eyes (9.09%). In these eyes, ICL removal and cataract surgery was performed. CONCLUSIONS: In our experience, ICL implantation in moderate and high ametropia was effective and relatively safe. The most common late complication was cataract formation. This complication can be managed effectively surgically with good refractive outcomes without loss of BCVA.
Keywords: dospělí; myopie; Female; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; lidé; hypermetropie; Hyperopia; pooperační komplikace; Treatment Outcome; následné studie; prognóza; retrospektivní studie; Follow-Up Studies; Male; Phakic Intraocular Lenses; Postoperative Complications; Young Adult; Lens Implantation, Intraocular; Prognosis; Myopia; mužské pohlaví; implantace nitrooční čočky; Retrospective Studies; fakické nitrooční čočky; Humans